The Liability Of Notaries For The Unlawful Acts Of Authentic Deeds - Riska Junita; T.Subarsyah (International Journal of Latin Notary, 2026)
This study examines the liability of the notary for the material truth of authentic deeds that subsequently give rise to unlawful acts. A notary is a public official authorised to prepare authentic deeds in respect of all legal acts, agreements, and declarations, in accordance with the law governing the position of the notary. The research employs a normative juridical method, drawing on library-based legal sources supplemented by field research. The study adopts a descriptive-analytical specification with a normative analytical method. The findings show that the notary’s responsibility is to ensure that the procedure for preparing the deed complies with the law, but the notary does not bear responsibility for the material truth of the contents of the deed, which originate from the appearing parties. Where a notary commits a fault or omission in respect of the material aspects of an authentic deed, causing loss to others and giving rise to an unlawful act that can be proved, the notary may be held administratively accountable through sanctions ranging from reprimand to dismissal, civilly accountable through the payment of damages, and criminally accountable; where it is proved that the notary intentionally or knowingly prepared, conspired in, or signed a false deed, he or she is subject to criminal liability for complicity in the forgery of a deed.